Characterization of Foot Arch among Male Office Workers in Selangor - Mohd Shariff, Shaliza; Raubel, Nur Afini; Shahlal, Norazmi; Mat Mazelan, Muhamad Zharin Hariz (Environment-Behaviour Proceedings Journal, 2024)
This study aims to identify the type of foot arch among male office workers in Selangor. A total of 100 participants aged 20 to 50 years participated. The arches were determined using the Harris-imprint index parameter. Analysis showed that normal arch 71% (n=71) 0.23 (±0.09), high arch (28%) 0.18 (±0.10), and flat arch (1%). Additionally, 55% (p<0.001; or 4.850) experienced discomfort with the shoe insoles, while 36% (n=36) had the same pair for the left and right foot, and 64% (n=64) had different pairs of foot arches. Findings revealed a different foot arch between their left and right feet.